EFFECTS OF SEXUALITY ON COMMON MENTAL DISORDERS AND QUALITY OF LIFE IN ELDERLY PEOPLE - Souza Júnior, Edison Vitório de; Cruz, Diego Pires; Siqueira, Lais Reis; Silva Filho, Benedito Fernandes da; Cairo, Gabriel Magalhães; Infante, Lucas Dias Brito; Sawada, Namie Okino (Cogitare Enfermagem, 2022)
Objective: to analyze the effects of sexuality on common mental disorders and quality of life in elderly people. Method: cross-sectional study conducted with 721 elderly people from all regions of Brazil who answered four instruments: bio-sociodemographic, EVASI, SRQ-20 and WHOQOL-Old between July and October 2020. Data were analyzed using Mann-Whitney and Structural Equation Modeling tests adopting a 95% confidence interval. Results: sexuality exerted a strong, positive effect on quality of life (SC=0.778 [95%CI=0.680-0.862] p<0.001), while on common mental disorders, the effect was strong and negative (SC=-0.481 [95%CI=-0.540 - -0.421] p<0.001). Conclusion: because a strong effect on the variables was identified, the clinical relevance of sexuality being worked on more frequently in health services was verified. Thus, society benefits with the insertion of a little explored theme and with the weakening of existing prejudices, including among the elderly themselves.